Correction: Pseudo electron-deficient organometallics: limited reactivity towards electron-donating ligands. Issue 5 (22nd January 2020) - Pitto-Barry, Anaïs; Lupan, Alexandru; Saidykhan, Amie; Zegke, Markus; Swift, Thomas; Attia, Amr A. A.; Lord, Rianne M.; Barry, Nicolas P. E.
Abstract : Correction for 'Pseudo electron-deficient organometallics: limited reactivity towards electron-donating ligands' by Anaïs Pitto-Barry et al., Dalton Trans., 2017, 46, 15676–15683.